2012
DOI: 10.1091/mbc.e11-10-0850
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional ultrastructure of the septin filament network inSaccharomyces cerevisiae

Abstract: Septins are essential for membrane compartmentalization and remodeling. Electron tomography of yeast bud necks shows filaments perpendicular and parallel to the mother-bud axis that resemble in vitro septin arrays. Filaments are still present, although disordered, in mutants lacking a single septin, underscoring the importance of septin assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
106
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 62 publications
8
106
0
Order By: Relevance
“…For example, purified Shs1-capped hetero-octamers form elaborate spirals, rings, and "bird nest" structures in vitro, whereas hetero-octamers capped with Shs1(S259D) form instead a meshwork-like structure with a regularly repeating pattern . Such a gauze-like arrangement of filaments (attributed to septins by antibody decoration) was observed at the bud neck when replicas of fixed yeast spheroplasts were examined after "unroofing" by freeze fraction and deep etching (Rodal et al 2005) and lattices of crisscrossed filaments thought to be septins have been seen in more recent EM analysis of the structures assembled at the bud neck (Bertin et al 2012;Ong et al 2014). However, when present as the sole source of Shs1, neither Shs1(S259A) nor Shs1(S259D) had any effect on the ability of Shs1 to support growth in three different Shs1-dependent strain backgrounds (Figure 1, D-F), and otherwise wild-type cells expressing either Shs1(S259A) or Shs1(S259D) as the sole source of this subunit have a normal morphology (data not shown).…”
Section: Phosphorylation Of Shs1 Within Its Cte Is Not Required For Fmentioning
confidence: 87%
See 2 more Smart Citations
“…For example, purified Shs1-capped hetero-octamers form elaborate spirals, rings, and "bird nest" structures in vitro, whereas hetero-octamers capped with Shs1(S259D) form instead a meshwork-like structure with a regularly repeating pattern . Such a gauze-like arrangement of filaments (attributed to septins by antibody decoration) was observed at the bud neck when replicas of fixed yeast spheroplasts were examined after "unroofing" by freeze fraction and deep etching (Rodal et al 2005) and lattices of crisscrossed filaments thought to be septins have been seen in more recent EM analysis of the structures assembled at the bud neck (Bertin et al 2012;Ong et al 2014). However, when present as the sole source of Shs1, neither Shs1(S259A) nor Shs1(S259D) had any effect on the ability of Shs1 to support growth in three different Shs1-dependent strain backgrounds (Figure 1, D-F), and otherwise wild-type cells expressing either Shs1(S259A) or Shs1(S259D) as the sole source of this subunit have a normal morphology (data not shown).…”
Section: Phosphorylation Of Shs1 Within Its Cte Is Not Required For Fmentioning
confidence: 87%
“…Because loss of the function of these proteins prevents cytokinesis and cell septation, and they seemed to be integral components of the filamentous structures erected at the bud neck, they were dubbed septins (Sanders and Field 1994;Pringle 2008). Indeed, subsequent purification of these proteins from yeast (Frazier et al 1998), and their production as recombinant proteins in bacteria Versele and Thorner 2004;Farkasovsky et al 2005), demonstrated that Cdc3, Cdc10, Cdc11, and Cdc12 were necessary and sufficient for the formation of long-paired filaments in vitro (Bertin et al 2008) the bud neck in vivo (Bertin et al 2012;Ong et al 2014). Detailed ultrastructural analysis led to the discovery that the septin complex that is the fundamental building block of the yeast filaments is a linear, hetero-octameric rod, with the order Cdc11-Cdc12-Cdc3-Cdc10-Cdc10-Cdc3-Cdc12-Cdc11 (Bertin et al 2008), which polymerizes end-on-end via Cdc11-Cdc11 interaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The released Cdc14, in turn, promotes mitotic exit by inactivating CDK1 activity and promotes cytokinesis by a mechanism that is not fully understood (see more discussion later). The precise architecture of the septin rings and hourglasses remains unclear, but undoubtedly, the hourglass contains septin filaments both perpendicular and parallel to the mother-daughter axis [Byers and Goetsch, 1976;DeMay et al, 2011;Bertin et al, 2012]. Fluorescence recovery after photobleaching analysis indicates that the nascent septin ring is dynamic, the hourglass is stable, and the double rings are dynamic again [Caviston et al, 2003;Dobbelaere et al, 2003].…”
Section: Septin Structures and Dynamics In Vivomentioning
confidence: 99%
“…The five mitotic septins of the budding yeast Cdc3p, Cdc10p, Cdc11p, Cdc12p and Shs1p form an octameric septin rod (Pringle, 2008). Septin rods assemble into non-polar filaments and other higher-order structures that appear as rings or collars at the bud neck of the cells (Bertin et al, 2008;Bertin et al, 2012;Byers and Goetsch, 1976;Haarer and Pringle, 1987). Septins mark the site of cell separation at the end of each cell cycle.…”
Section: Introductionmentioning
confidence: 99%